Temperature effects on the mechanical properties of hybrid composites reinforced with vegetable and glass fibers. (October 2020) - Cerbu, Camelia; Wang, Huaiwen; Botis, Marius Florin; Huang, Zhen; Plescan, Costel
Highlights: Tensile properties at different temperatures were measured for hybrid composite reinforced with vegetable and glass fibers. Finite element analysis was conducted to compute residual thermal stresses developed in fibers and matrices at interfaces. Microscopic photos of the specimen made hybrid composite highlight the detachments of fibers from epoxy matrix. Residual thermal stresses developed at the fiber-matrix interface lead to the detachment of fibers from the epoxy resin. The highest reduction in tensile strength was recorded for hybrid composites reinforced with vegetable and glass fibers. Abstract: Although there are numerous applications for composite materials reinforced with vegetable textile fibers in outdoor parts and components (e.g., acoustic or thermal insulation panels in construction, furniture for gardens), only a few studies have reported the effects of temperature on hybrid composites reinforced with both glass and vegetable fibers. The main goal of this study was to analyze the effects of temperature on the tensile properties of five types of polymeric composites with different reinforcements: jute fabric, glass and jute fabric, flax fabric, glass and flax fabric, and glass fabric. Our method consisted of tensile testing all five types of composites at room temperature (20 °C) and other different temperatures (50 °C and 70 °C). The greatest values of reduction in tensile strength were recorded for hybrid composites. Reductions of 42.3% and 49.6% at 50 °C and 70 °C, respectively, were observed for the composite reinforced with flax and glass fibers. Reductions of 34.6% and 60% at 50 °C and 70 °C, respectively, were observed for the composite reinforced with jute and glass fibers. Finite element analysis of representative volume elements was conducted to compute the residual thermal stresses developed in the fibers and in the matrices at interfaces. It was determined that the thermal stresses cause micro-cracks at the interfaces. Thermogravimetric analysis and microscopic analysis were also conducted to identify the causes of the significant decreases in tensile properties. The effects of the anisotropy of flax and jute fibers on the thermal stresses developed at fiber-matrix interfaces were analyzed as well.